Two-wheel balancing robot; review on control methods and experiments - Mohd Romlay, Mohamad Rabani; Mohd. Ibrahim, Azhar; Toha, Siti Fauziah; Rashid, Muhammad Mahbubur (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Two-wheel mobile robot has been active field of study and research as it provides simple mechanical design and high maneuverability. Various developments continue to take place in the process of achieving stability, navigation from one place to another. This article intended to address the control methods of balancing two-wheeled mobile robot from linear controller, non-linear controller and adapting and self-learning algorithm. The focus of the review will be the evaluation and experiment done on two-wheel mobile robot. With the objective of mobile robot advances further from self-balancing, navigating or obstacle avoiding, towards completing sophisticated external task such as transporting and monitoring the surrounding. It is believed that this review will help researchers in developing substantial two-wheeled mobile robot.